PENGARUH CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM PADA PRODUK SCARLETT WHITENING DI SURABAYA - Yuliana Jamilatul Azizah; Khusnul Fikriyah (Komitmen: Jurnal Ilmiah Manajemen, 2023)
There are many beauty products in the market competition. But there are several factors that influence consumers when making purchasing decisions. In this study using the celebrity endorsement factor and the formulation of the problem is whether the celebrity endorsement influences the purchasing decisions of Muslim consumers on scarlett whitening products in Surabaya. The purpose of this research is to find out whether celebrity endorsements influence the decision of Muslim consumers to buy Scarlett Whitening products in Surabaya. The type of research used is associative quantitative. Questionnaires were distributed to 100 respondents who were selected using a purposive sampling technique with the number of samples using the formula Heir et al. Respondents' answers were measured using a Likert scale. This study shows that celebrity endorsement as an independent variable has an influence on purchasing decisions as the dependent variable of 17.3% (R2). This study has managerial implications for producers/sellers, where celebrity endorsements are important in attracting Muslim consumers to make purchasing decisions on Scarlett Whitening products in Surabaya.